(untitled) (Jurnal Simki Postgraduate, 2023)
The purpose of this study was to determine the validity, and practicality of magnetic board pop up media for the human digestive system. This research is a development research that uses the ADDIE model. Data collection instruments in this study were observation, interviews, and questionnaires. The data analysis technique used is quantitative data analysis techniques in the form of scores on questionnaires. The results of this study were that the human digestive system magnetic board pop up media was stated to be very valid with a percentage of 82% of media validation and 98% of material validation. The magnetic board pop up media for the human digestive system was stated to be very practical with the results of the teacher’s response questionnaire reaching 94% in the limited trial and 84% in the wide trial. Student response questionnaires reached 98% in limited trials and 97% in large trials.